Assessment of Different Forms of Urea on Growth, Yield and Nitrogen Use Efficiency of Rice - M. R. Islam; S. B. Z. Sharna; S. Islam; M. Jahiruddin (Recent Progress in Plant and Soil Research Vol. 4, 2021)
Nitrogen is one of the most deficient plant nutrients in Bangladesh soils. The nitrogenous fertilizer especially prilled urea is a commonly used fertilizer for rice production but its efficiency is very low under traditional broadcast method. Urea is available as prilled urea, urea supergranule and also as NPK briquette for use by the framers. A field experiment was carried out in the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh on Aus rice (May-August) during the cropping season of 2014 to assess the effects of different forms of urea (prilled urea, urea briquette and NPK briquette) on growth, yield, and nitrogen use efficiency of BRRI dhan48. There were six treatments as T1 [check (N0P16K42], T2 [Urea briquette (one-3.4 g) (N52P16K42)], T3 (Urea briquette (one - 2.7 g (N78P16K42)], T4 [NPK briquette (one-3.4g) (N51P13K32], T5 [prilled urea (N78P16K42)] and T6 [NPK briquettes (two - 2.4 g briquettes (N78P15K42)]. The experiment was laid out in a Randomized Complete Block Design with four replications. Prilled urea was applied in two equal splits; at 8 days after transplanting (DAT) and the second split after 38 DAT, while for urea briquettes and NPK briquettes were deep placed (8-10 cm depth) at 8 DAT between four hills at alternate rows. Water samples from each treatment of rice fields were collected after first split application of urea and deep placement of urea briquette and NPK briquette and the second sampling was done after second split of urea. Every sampling was done consecutively for 7 days for measuring NH4+-N. The results showed that the NH4+-N concentration in rice field water reached to maximum on day 2 in PU treated plots and then decreased with time, while in urea briquettes and NPK briquettes treated plots has very low amount of NH4+-N in the rice field water. The highest grain yield of 4.75 t ha-1 (69% over control) was obtained in the treatment T3. The treatment T3 also produced the highest straw yield of 5.49 t ha-1. The maximum apparent N recovery and the maximum N use efficiency were found in the treatment T4. Deep placement of urea briquettes and NPK briquettes reduced N-losses and enhanced the recovery of applied N as well as N use efficiency in comparison with PU application.